Flavours of life: assessing the feeding activity & preferences of soil-leaf litter invertebrates across a forest disturbance gradient - Tay, Li Si (Nanyang Technological University, 2022)
Decomposition is one of the most important processes in terrestrial ecosystems and main contributors to this process include soil and leaf litter invertebrates. These invertebrates are involved in all stages of decomposition and play crucial ecological roles. However, their communities and the roles they perform are known to be affected by forest disturbance. In this study, we use the bait lamina test system to compare the feeding activity of invertebrates, as a proxy for decomposition, across a forest disturbance and restoration gradient (primary, secondary, restored, degraded). This simple and inexpensive method quantifies the amount of bait consumed to approximate feeding activity. In addition to using bait lamina sticks typically employed to measure soil feeding activity, we developed a novel application of this method to measure feeding activity in the leaf litter layer, using 3D-printed bait lamina cards. We then deployed different bait flavours made using standard bait (wheat bran) and native plant species representing each forest type (Shorea curtisii, Macaranga bancana, Koompassia malaccensis, Dicranopteris linearis). Our results showed that standard bait was preferentially consumed in both soil and leaf litter. Further analysis with standard bait excluded found slightly lower feeding activity in primary forests for the soil layer and strong preference for M.bancana bait for the leaf litter layer. Altogether, these findings suggest that feeding activity is largely unaffected by forest disturbance, and they highlight a potential nature-based application of M.bancana litter as an organic fertiliser or mulch in forest restoration and sapling cultivation efforts.